The development and maturation of the ovary of Parechinus angulosus (Echinodermata, Echinoidea) - Ferreira, Vivienne C.(Vivienne Catherina) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1989.